Evaluation of the TAEP4.0 by Basic Education Teachers: a Case Study in the Context of Education 4.0 - Silva, Deivid Eive dos S.; Corrêa Sobrinho, Marialina; Valentim, Natasha Malveira C. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2022)
Education 4.0 is characterized as a learning paradigm to prepare students for life in the 21st-Century. Thus, a website was created, called TAEP4.0, that aims to support teachers of Basic Education in creating projects based on Education 4.0. This paper presents the evaluation of TAEP4.0. In this case study, the teachers used the TAEP4.0 to carry out projects in the Informatics lab. Then, the teachers answered a questionnaire about their experiences to verify the impacts of TAEP4.0 on their work. The results indicated that the TAEP4.0 allowed teachers to rethink the resources to compose their class, allowing the inclusion of Informatics in classes. Overall, the evaluation performed can improve and broaden teachers’ interaction with the TAEP4.0 and its resources.